EFFECT OF SUCROSE AND AUXIN CONCENTRATION ON INDUCTION OF In Vitro ADVENTITIOUS ROOTS OF Withania somnifera - D. PRADEEPA; R. KALAISELVI; T. PANKAJAVALLI; KALAISELVI SENTHIL (International Journal of Pharma and Bio Sciences, 2014)
The genus Withania is an important member of the family Solanaceae, Twenty-three species of the genus Withania have been reported. Of these, only two species namely Withania somnifera and Withania coagulans have been reported from India Withania somnifera, popularly known as "Indian Ginseng". Roots of this plant contain important secondary metabolite withanolide, which have many pharmacological activities. In the present study we induced in vitro adventitious root from the leaf explants of Withania somnifera, was achieved on full strength Murashige and Skoog’s medium (MS medium) supplemented with 45g/ L sucrose, and different concentration of auxins. Basal medium supplemented with 1mg/ L indole butyric acid (IBA) and 1mg/ L indole acetic acid (IAA) achieved the maximum number of roots with 100% response. The roots were transferred to full strength MS suspension medium supplemented with the above combination of auxins and incubated on an orbital shaker at 100rpm at 25±2°C. Adventious roots were harvested after 10th and 25th day of inoculation, and growth index was found to be 0.06 and 30.27 respectively.